2015
DOI: 10.3109/17453674.2015.1041846
|View full text |Cite
|
Sign up to set email alerts
|

No effect of risedronate on femoral periprosthetic bone loss following total hip arthroplasty

Abstract: Background and purpose We have previously shown that during the first 2 years after total hip arthroplasty (THA), periprosthetic bone resorption can be prevented by 6 months of risedronate therapy. This follow-up study investigated this effect at 4 years.Patients and methods A single-center, double-blind, randomized placebo-controlled trial was carried out from 2006 to 2010 in 73 patients with osteoarthritis of the hip who were scheduled to undergo THA. The patients were randomly assigned to receive either 35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Many nonimplant-related factors including age, sex, BMI, primary disease, bone quality, osteoporosis treatment, and daily activity might have potential impact on periprosthetic bone remodeling [72][73][74], although subgroup analyses indicated no correlation between periprosthetic BMD change and primary disease or BMI. Noticeably, bone remodeling around prosthesis in the patients with AVN will be permanently influenced by primary disease [75], the difference might be gradually increased in long-term follow-up, and antiosteoporosis therapy should be highly recommended in this population.…”
Section: Nonimplant-related Factorsmentioning
confidence: 95%
“…Many nonimplant-related factors including age, sex, BMI, primary disease, bone quality, osteoporosis treatment, and daily activity might have potential impact on periprosthetic bone remodeling [72][73][74], although subgroup analyses indicated no correlation between periprosthetic BMD change and primary disease or BMI. Noticeably, bone remodeling around prosthesis in the patients with AVN will be permanently influenced by primary disease [75], the difference might be gradually increased in long-term follow-up, and antiosteoporosis therapy should be highly recommended in this population.…”
Section: Nonimplant-related Factorsmentioning
confidence: 95%
“…No gray literature was included. Finally, four RCTs [ 14 – 17 ] published between 2006 and 2015 were included in the present meta-analysis; these studies included 97 patients in the experimental groups and 101 patients in the control groups. The duration follow-up ranged from 6 months to 4 years.…”
Section: Resultsmentioning
confidence: 99%
“…All studies reported allocation concealment by closed envelope or other techniques. Double blinding was reported in two RCTs [ 16 , 17 ]; however, none of the included studies attempted to blind the assessors. An intention-to-treat analysis was not performed in any of the RCTs; therefore, a potential risk of type II statistical error existed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations